KETERTARIKAN MAHASISWA JURUSAN MANAJEMEN TRANSPORTASI UDARA UNTUK MENJADI ENTREPRENEUR DALAM INDUSTRI JASA ANGKUTAN UDARA - Sugiarti Sugiarti (Aliansi : Jurnal Manajemen dan Bisnis, 2019)
This research aims to examine the interest of students majoring in Air Transportation Management to become entrepreneurs in the air transport service industry. The hypothesis of this study discusses whether students already have an understanding of self-knowledge, entrepreneurship character, and interest in students majoring in transportation management to become entrepreneurs in the air transportation services industry. Based on the self-recognition test questionnaire distributed to 84 students, it was found that there were 48 students who were very strong in knowing and evaluating themselves. There are 30 students who are strong in knowing and evaluating themselves. There are 6 students who are sufficient to know and assess themselves. Based on the entrepreneurships character test, the results of the analysis note that there are 65 students who have entrepreneurships character and there are 19 students who do not have entrepreneurships character. Based on the test in the field of air transportation service business that is of interest to students, it is found that there are 16 students who, if they have graduated, are interested in becoming entrepreneurs in the cargo business. There are 35 students who, if they have graduated, are interested in becoming entrepreneurs in the field of tour and travel. There are 16 students who, if they have graduated, are interested in becoming entrepreneurs in the catering business. There are 10 students who, if they have graduated, are interested in becoming entrepreneurs in the field of ground handling business. There are 7 students who, if they have graduated, are interested in becoming entrepreneurs in other fields and working in the aviation industry.